Current and future biomarkers for pancreatic adenocarcinoma - Sven H Loosen; Ulf P Neumann; Christian Trautwein; Christoph Roderburg; Tom Luedde (Tumor Biology)
Although pancreatic cancer is only the twelfth most common type of cancer in the world, it features a very unfavorable prognosis. The mortality rate almost equals the incidence rate, corroborating the very poor prognosis of pancreatic cancer. The 5-year survival rate for all stages of pancreatic ductal adenocarcinoma is only 7%. Surgical resection represents the only potentially curative treatment option for pancreatic ductal adenocarcinoma patients but is often not feasible due to the advanced stage of the disease upon diagnosis. For advanced disease, palliative chemotherapy is the treatment of choice although the regimens available to date are untargeted and have extensive side-effect profiles, making them unsuitable for patients with a low performance status. For this reason, early detection of pancreatic cancer is essential in order to provide patients with an optimal therapeutic approach. Up to the present day, carbohydrate antigen 19-9 is the only diagnostic marker approved by the U.S. Food and Drug Administration but its diagnostic potential is limited due to its restricted sensitivity and specificity, supporting the urgent need for novel biomarkers. In addition, prognostic and treatment-predictive biomarkers might provide essential information regarding personalized treatment decisions for individual patients. In this article, we aim to review current and future diagnostic, prognostic, and treatment-predictive biomarkers for pancreatic cancer.